Deep Learning with Project-Based Learning (PjBL) Model for Student Creativity: Pembelajaran Mendalam dengan Model Project-Based Learning (PjBL) untuk Kreativitas Siswa - Nurazizah, Zhafira; Mubarok, As’ad Syamsul; Herawan, Endang; Putri , Dian Permana (Universitas Muhammadiyah Sidoarjo, 2025)
21st-century education requires students not only to master basic knowledge but also to develop critical thinking, creativity, and problem-solving skills—competencies that can be fostered through the Project-Based Learning (PjBL) model within the framework of deep learning. This study aims to explore how the implementation of PjBL can enhance students' creativity through five key indicators: fluency, flexibility, originality, elaboration, and emotional engagement with enthusiasm. Using a descriptive qualitative approach, this case study was conducted with eighth-grade students at a public junior high school in Cirebon Regency. Data were collected through observation, interviews, and analysis of student project documents, and analyzed using the interactive model of Miles and Huberman. The findings show that PjBL creates an open and contextual learning environment, encouraging students to actively explore ideas, think from multiple perspectives, and generate original, meaningful solutions. PjBL also fosters high learning enthusiasm and strengthens students’ emotional involvement in the learning process. The study implies that integrating PjBL into deep learning approaches holds great potential for cultivating a collaborative, reflective, and creative learning culture. These findings highlight the crucial role of teachers as facilitators and designers of learning experiences that stimulate students’ creativity in authentic and meaningful contexts. Highlights: PjBL supports key creativity indicators: fluency, flexibility, originality, elaboration, and emotional engagement. The model fosters active, contextual learning and encourages original problem-solving. Teachers play a central role as facilitators in designing meaningful learning experiences. Keywords: Project-Based Learning, Creativity, Deep Learning, Student Engagement, 21st-Century Skills